2015
DOI: 10.1016/j.jenvrad.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-resolved analyses of aerodynamic fallout from a uranium-fueled nuclear test

Abstract: Five silicate fallout glass spherules produced in a uranium-fueled, near-surface nuclear test were characterized by secondary ion mass spectrometry, electron probe microanalysis, autoradiography, scanning electron microscopy, and energy-dispersive x-ray spectroscopy. Several samples display compositional heterogeneity suggestive of incomplete mixing between major elements and natural U ((238)U/(235)U = 0.00725) and enriched U. Samples exhibit extreme spatial heterogeneity in U isotopic composition with 0.02 < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…Recent work analyzing fallout from other nuclear tests focus on determining formation conditions and how device materials incorporated into glassy fallout [54,55,56]. The characterization of stable noble gasses has confirmed that historical fallout preserves a record of the relative volatilities of some fission products, though the distribution was not spatially determined in this study [54].…”
Section: Contemporary Fallout Researchmentioning
confidence: 64%
See 4 more Smart Citations
“…Recent work analyzing fallout from other nuclear tests focus on determining formation conditions and how device materials incorporated into glassy fallout [54,55,56]. The characterization of stable noble gasses has confirmed that historical fallout preserves a record of the relative volatilities of some fission products, though the distribution was not spatially determined in this study [54].…”
Section: Contemporary Fallout Researchmentioning
confidence: 64%
“…The average major element oxide composition of the interiors of agglomerated fallout objects exhibit a different compositional range than the values found in mm-scale objects [55,56] In the following section, the Si data are not presented, as the Si content across the interfaces and the samples themselves is not highly variable (<2.9% standard deviation for the entire dataset). The K data are also not presented, given their similarity to the Na data (as shown by EDS, Figure 3.26).…”
Section: Epma Analysesmentioning
confidence: 97%
See 3 more Smart Citations